One-step prepared prussian blue/porous carbon composite derives highly efficient Fe–N–C catalyst for oxygen reduction. (29th May 2020) - Yin, Pengfei; Wang, Wenli; Rao, Hanbing; Wang, Guangtu; Sun, Mengmeng; Jiang, Yuanyuan; Wang, Yanying; Zou, Ping; Wang, Xianxiang; Zhao, Qingbiao; Lu, Zhiwei
Abstract: Preparation of high-efficiency oxygen reduction reaction (ORR) catalysts with abundant and inexpensive biomass materials have been a hot research topic. We use nitrogen-rich lentinus edodes and potassium ferrate (K2 FeO4 ) to simultaneously activate the carbon material and prepare prussian blue (PB), and a porous carbon composite (PB/C) containing PB is synthesized. Finally, using ammonium chloride (NH4 Cl) as a nitrogen source to further synthesize a Fe–N–C catalyst (PB/CN1 T800 ) containing a trace amount of Fe for ORR. Results show that the prepared PB/CN1 T800 catalyst forms a coral-like structure, which mainly contains mesopores and possesses a large specific surface area of approximately 1582 m 2  g −1 . Moreover, the onset potential of PB/CN1 T800 is 0.95 V, and the half-wave potential is 0.83 V, which are consistent with those of commercial Pt/C. Thus the PB/CN1 T800 material is an ORR catalyst with excellent performance. This work provides a basis for simple and efficient conversion of rich biomass into PB/porous carbon composites to prepare highly efficient catalysts. Graphical abstract: Here is a new method for simultaneously preparing prussian blue and porous carbon materials by using biomass and potassium ferrate as raw materials. This is the first time that the two processes of biomass carbon activation and prussian blue preparation are combined, realizing the use and innovation of the original method of prussian blue preparation. Besides, using the prussian blue/porous carbon as an intermediate to derive a highly efficient Fe–N–C catalyst for oxygen reduction is also a new way. Image 1 Highlights: One-step synthesis of PB/porous carbon composites from nitrogen-rich biomass. K2 FeO4 as both activator and iron source for preparing PB/porous carbon composites. Nitrogen doping of PB/porous carbon composites to prepare Fe–N–C materials. A new Fe–N–C material with high ORR catalytic activity is prepared.